PEMBERDAYAAN MASYARAKAT MELALUI PENGEMBANGAN AGROWISATA SALAK WEDI - Nur Hamid; Dyah Yulia Ningsih; Agus Riyadi (Nindikayla Institute, 2022)
Wedi Village is one of the areas in Bojonegoro Regency, East Java, where the community can take advantage of its natural potential. The development of Salak Wedi Agrotourism is one of the community empowerment programs to develop the potential of a village to improve the welfare of the community. Therefore, the author formulates the problem as follows: (1) How is the process of community empowerment through the development of Salak Wedi Agrotourism by the Wedi Village Tourism Awareness Group. (2) How is the community empowerment model through the development of Salak Wedi Agrotourism by the Wedi Village Tourism Awareness Group. This study uses a qualitative method with a descriptive approach. The data collection techniques through observation, interviews, and documentation. In this study, researchers were directly involved in extracting data. Analysis of the data used using the theory of Milles and Haberman, which includes data reduction, data exposure, and conclusion. This study indicates that: (1) the community empowerment process through the development of Salak Wedi Agrotourism goes through several stages, namely the problem posing stage, problem analysis stage, goal setting stage (aims) and targets (objectives), action plans stage, the implementation stage of activities, and the evaluation stage. (2) the community empowerment model through the development of Salak Wedi Agrotourism conducted in Wedi Village is a bottom-up model. The model uses the concept of community participation in all empowerment processes because with participation in the community, the community is placed as a subject. In addition, the community development empowerment model is also used, which is an empowerment model that is carried out through the development of the potential of natural resources and human resources assisted by facilitators.